2015
DOI: 10.1186/s13041-015-0153-7
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 activity is required for the reconsolidation and extinction of contextual fear memory

Abstract: BackgroundMemory consolidation, reconsolidation, and extinction have been shown to require new gene expression. Poly ADP-ribosylation mediated by poly (ADP-ribose) polymerase-1 (PARP-1) is known to regulate transcription through histone modification. Recent studies have suggested that PARP-1 positively regulates the formation of long-term memory (LTM); however, the roles of PARP-1 in memory processes, especially processes after retrieval, remain unknown.ResultsHere, we show critical roles for PARP-1 in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 71 publications
2
34
0
Order By: Relevance
“…The hippocampus is known to play an essential role in the consolidation and reconsolidation of contextual fear memory (Alberini, 2005;Anagnostaras et al, 2001;Debiec et al, 2002;Inaba et al, 2015;Kim et al, 1993;Lee et al, 2004;Mamiya et al, 2009;Phillips & LeDoux, 1992;Suzuki et al, 2008;Tronson & Taylor, 2007). We found that inhibiting hippocampal N-glycosylation blocked the consolidation and reconsolidation of contextual fear memory, suggesting that the induction of de novo N-glycosylation in the hippocampus in response to learning or retrieval plays a critical role in hippocampus-dependent memory consolidation and reconsolidation.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…The hippocampus is known to play an essential role in the consolidation and reconsolidation of contextual fear memory (Alberini, 2005;Anagnostaras et al, 2001;Debiec et al, 2002;Inaba et al, 2015;Kim et al, 1993;Lee et al, 2004;Mamiya et al, 2009;Phillips & LeDoux, 1992;Suzuki et al, 2008;Tronson & Taylor, 2007). We found that inhibiting hippocampal N-glycosylation blocked the consolidation and reconsolidation of contextual fear memory, suggesting that the induction of de novo N-glycosylation in the hippocampus in response to learning or retrieval plays a critical role in hippocampus-dependent memory consolidation and reconsolidation.…”
Section: Discussionmentioning
confidence: 82%
“…To assess this possibility, we examined the effects of inhibiting N-glycosylation on the expression of c-fos, whose expression is dependent upon neuronal activity (Frankland, Bontempi, Talton, Kaczmarek, & Silva, 2004;Inaba et al, 2015;Sheng, McFadden, & Greenberg, 1990;Strekalova et al, 2003). We measured the number of c-fos-positive cells in the hippocampal CA1 region at 90 min after training for contextual fear using immunohistochemistry.…”
Section: N-glycosylation Is Required For C-fos Induction Following Trmentioning
confidence: 99%
See 3 more Smart Citations